2015
DOI: 10.1016/j.ijrobp.2014.09.045
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Hypoxia PET Tracers [18F]HX4, [18F]FAZA, and [18F]FMISO in a Preclinical Tumor Model

Abstract: This study indicates that each tracer has its own strengths and, depending on the question to be answered, a different tracer can be put forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 30 publications
3
100
0
Order By: Relevance
“…However, these results were obtained at 80–90 min post injection, a time point which is probably too early for evaluation since normal tissue clearance is still ongoing. Cu-ATSM had the highest tumour accumulation and low renal clearance compared to fluorinated nitroimidazoles Peeters et al [211]In a comparative study within a rat rhabdomyosarcoma model, FMISO, FAZA, and HX4 uptake (tumour to blood ratio (TBR)), reproducibility and reversibility were assessed. Blood clearance for FAZA and HX4 was similar 3 h p.i., while for FMISO, as expected, clearance from normal tissues was significantly lower.…”
Section: Methodsmentioning
confidence: 99%
“…However, these results were obtained at 80–90 min post injection, a time point which is probably too early for evaluation since normal tissue clearance is still ongoing. Cu-ATSM had the highest tumour accumulation and low renal clearance compared to fluorinated nitroimidazoles Peeters et al [211]In a comparative study within a rat rhabdomyosarcoma model, FMISO, FAZA, and HX4 uptake (tumour to blood ratio (TBR)), reproducibility and reversibility were assessed. Blood clearance for FAZA and HX4 was similar 3 h p.i., while for FMISO, as expected, clearance from normal tissues was significantly lower.…”
Section: Methodsmentioning
confidence: 99%
“…In a second comparative study, 18 F-HX4 and 18 F-FAZA were found to be sensitive to an increase of hypoxia, induced by the breathing of a gas mixture containing 7% O 2 , when the tumor-to-blood ratio was used. However, when only the tumor-to-muscle was used, only 18 F-FAZA revealed a significant decrease in tumor oxygenation (41). …”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…The call for more individualized approach to cancer treatment challenges future studies to investigate prospectively whether risk stratification of patients by means of metabolic parameters will lead to change of management and significant improvement in patients’ survival. Moreover, it should be recognized that the benefit of PET imaging can be extended by using different tracers for different biological features such as hypoxia level, which in turn is associated with negative effect on prognosis [3739]. Perhaps this can lead to promising risk stratification tools that combine different biological imaging markers based on an entirely non-invasive method.…”
Section: Discussionmentioning
confidence: 99%